Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1086/664999
|View full text |Cite
|
Sign up to set email alerts
|

Population Responses to Perturbations: The Importance of Trait-Based Analysis Illustrated through a Microcosm Experiment

Abstract: Environmental change continually perturbs populations from a stable state, leading to transient dynamics that can last multiple generations. Several long-term studies have reported changes in trait distributions along with demographic response to environmental change. Here we conducted an experimental study on soil mites and investigated the interaction between demography and an individual trait over a period of nonstationary dynamics. By following individual fates and body sizes at each lifehistory stage, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 60 publications
(69 reference statements)
1
49
0
Order By: Relevance
“…Given that body size had a significant effect on all vital rates ( β 1 , β 4 in Table ), understanding thermal responses requires understanding how temperature affects body size and emphasizes the importance of a trait‐based approach when investigating population dynamics (Ozgul et al., ; Ronget, Garratt, Lemaître, & Gaillard, ). For all vital rates except clutch size, the best model included a temperature effect, and in four of six vital rates, this effect was significant.…”
Section: Discussionmentioning
confidence: 99%
“…Given that body size had a significant effect on all vital rates ( β 1 , β 4 in Table ), understanding thermal responses requires understanding how temperature affects body size and emphasizes the importance of a trait‐based approach when investigating population dynamics (Ozgul et al., ; Ronget, Garratt, Lemaître, & Gaillard, ). For all vital rates except clutch size, the best model included a temperature effect, and in four of six vital rates, this effect was significant.…”
Section: Discussionmentioning
confidence: 99%
“…The randomly variable treatment was designed to be entirely unpredictable with daily food provisions being chosen from a random distribution with a mean of two balls over a 56-day window, with a maximum daily provision of 12 balls . The mite populations were censused each week for 2 years, where a generation is approximately 5 weeks (Ozgul et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Analyses of empirical data demonstrates that eco-evolutionary feedback from an environmental change to population dynamics could explain observed trait distributions and population sizes Ozgul et al, 2010Ozgul et al, , 2012, but this generally lacks evidence of genetic selection, but see similar studies of trait demography in birds (Charmantier et al, 2008;Nussey et al, 2005). Other studies have identified where ecoevolutionary dynamics are likely to occur, for example, by demonstrating how changes in selection have led to changes in animal behaviour and/or distribution (Strauss et al, 2008).…”
Section: Eco-evolutionary Population Dynamics-the Full Loopmentioning
confidence: 97%
See 1 more Smart Citation
“…A (nonexhaustive) review of published IPMs reveals that the shape of the bulb mite character-demography functions are comparable to those of other species (e.g., Soay sheep Ovis aries (Coulson et al 2010); soil mite Sancassania berlesei (Ozgul et al 2012); Nile crocodile Crocodylus niloticus (Wallace et al 2012), except for the survival rate of adults in the bad environment as this is of an atypical hump shape ( fig. 1).…”
Section: Discussionmentioning
confidence: 85%